2021
DOI: 10.3389/fpsyg.2021.746823
|View full text |Cite
|
Sign up to set email alerts
|

Tracing an Unyielding Work Compulsion: A Moderated Mediation Model of Abusive Supervision and Compulsory Citizenship Behavior

Abstract: We conceptualize and examine an integrated model of compulsory citizenship behavior in the employees of the insurance sector. For this purpose, direct and indirect influences of job demands (active-aggressive and passive-aggressive abusive supervisions) are examined on the compulsory citizenship behavior. In so doing, the relevance of perceived support of coworkers as a job resource and emotional exhaustion as an underlying mechanism is investigated. Data were collected from 205 managerial level employees work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Hence, we believe that abusive supervision can negatively predict self-efficacy. In addition, as stated earlier, abusive supervision can cause stress, emotional exhaustion, burnout, and depression, and then decrease the motivation to engage in the job (Baig and Riaz, 2021). In the process, self-efficacy can efficiently regulate the predicament to achieve a desired balance between work attitude and behavior.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hence, we believe that abusive supervision can negatively predict self-efficacy. In addition, as stated earlier, abusive supervision can cause stress, emotional exhaustion, burnout, and depression, and then decrease the motivation to engage in the job (Baig and Riaz, 2021). In the process, self-efficacy can efficiently regulate the predicament to achieve a desired balance between work attitude and behavior.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies have linked abusive supervision to organization attitudes, behaviors, and work outcomes, indicating that abusive supervision has some deleterious consequences as follows. Baig and Riaz (2021) have reported that abusive supervision is positively associated with stress and emotional exhaustion. Other scholars have also found that abused subordinates may experience anxiety ( Huang et al, 2019 ), and insomnia ( Sannes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Related meta-analysis and empirical research results have shown that challenge stress appraisal induces employees' positive attitude, cognition and problem-solving stress coping strategies, thereby encouraging employees to perform more positive work behaviors; on the other hand, hindrance stress appraisal induces employees' negative attitude, cognition and more emotion-solving stress coping strategies, thereby making employees perform more negative work behaviors, such as counterproductive work behaviors. 31,32 Based on the cognitive appraisal theory of stress, and given that compulsory citizenship behavior not only causes loss of work autonomy, 33 but also brings employees obtain more benefits from extra-role behaviors, 34 compulsory citizenship behavior may evoke both challenge stress appraisal and hindrance stress appraisal of new generation employees, thus having both positive and negative effects on counterproductive work behavior at the same time. However, the degree to which compulsory citizenship behavior evoke challenge stress appraisal or hindrance stress appraisal may vary depending on the extent of compulsory citizenship behavior.…”
Section: Theoretical Background and Hypothesis Development The Nonlin...mentioning
confidence: 99%